Adjusment Basketball Facilities and Infrastructure for Children 10-12 Years Old Through Anthropometric Comparison - Hanik Liskustyawati; Baskoro Nugroho Putro; Rony Syaifullah ; Sri Santoso Sabarini ; Slamet Riyadi ; Agus Mukholid (Jurnal Pendidikan dan Pengajaran, 2023)
Implementation of physical education is allowed to modify instructional media. Physical education requires facilities and infrastructure specifically designed to promote physical activity. The aim of this research is to develop adjustments to basketball facilities and infrastructure for children aged 10-12 years through anthropometric comparisons. This research uses simple development research because it is still in the form of an initial design. The total research sample involved was 691 people. The sample underwent height, arm span, leg length, and finger span measurements. The results are that the comparison ratio of facilities and infrastructure for adults and children aged 10-12 years is the same as the anthropometric ratio of the study sample. Sports facilities and infrastructure adjustments are indispensable to the growth and development of children aged 10-12. By providing spaces where children can engage in physical activities tailored to their age and interests, we lay the foundation for healthy lifestyles, holistic skill development, cognitive growth, and emotional well-being.